Answer:
The equation perpendicular to y = 3x - 2 and passing through (-9, 0) in the slope-intercept form will be:
Explanation:
The slope-intercept form of the line equation
where
Given the line
y = 3x - 2
comparing with the slope-intercept form of the line equation
The slope of the line y = 3x - 2 is: m = 3
We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:
slope = m = 3
Thus, the slope of the the new perpendicular line = – 1/m = -1/3 = -1/3
The point-slope form of the line equation is:
where
- m is the slope of the line
In our case:
now substituting the perpendicular slope m = -1/3 and (-9, 0) in the point-slope form of the line equation
![y-0=-(1)/(3)\left(x-\left(-9\right)\right)](https://img.qammunity.org/2022/formulas/mathematics/college/jfbekkwzu4ktd123usp0ov37zneo3rxxli.png)
![y=-(1)/(3)\left(x-\left(-9\right)\right)](https://img.qammunity.org/2022/formulas/mathematics/college/6c8ez1pm94wt4qv2eusguz2p5jcyqkkid1.png)
![y=-(1)/(3)\left(x+9\right)](https://img.qammunity.org/2022/formulas/mathematics/college/swkk39ut08rfox5nqftx4ksoevutu8tvoi.png)
![\:\:y\:=-(1)/(3)x-3](https://img.qammunity.org/2022/formulas/mathematics/college/zksxv4ggpmucdhf6494qn1k49cs46cddlc.png)
Therefore, the equation perpendicular to y = 3x - 2 and passing through (-9, 0) in the slope-intercept form will be: